KESIAPAN SISTEM PENANGGULANGAN KEBAKARAN PADA GEDUNG FAKULTAS TEKNIK UNIVERSITAS SYIAH KUALA - Dede Hermansyah; Mochammad Afifuddin; Abdul Munir (Prodi Magister Teknik Sipil Unsyiah, 2018)
Fire hazard is one of the risks that must be considered in the building safety management. This study aims to determine the condition of fire risk in the Engineering Faculty Building, Syiah Kuala University Banda Aceh. The analysis used in this research is Hazard identification, Risk Assessment and Risk Control and descriptive analysis. Data were collected using questionnaire survey, interview, and observation. The purposive sampling method is used to determine the number of samples. A total of 238 samples were collected with target respondents are lecturers, employees, and students at the Faculty of Engineering, Syiah Kuala University. Observations were conducted at the Engineering Building of A1, A2, and A3. Further, we conducted a direct interview with an expert of the Occupational Health and Safety (OHS). The result from the analysis the value of firefighting unit counted on an average 688.7. It can be concluded that the condition of fire protection system preparedness in the building of Faculty of Engineering, Syiah Kuala University in bad condition. Furthermore, the result of the assessment of fire risk in administrative room, supporting room, lecture room, and library room obtained shows is a low risk, while as for the laboratory room categorize a high risk. Fire risk controls are needed as the most effective in implementing Occupational Health and Safety (OHS) management systems, including establishing OHS fire management institutions and fire safety coordinator of a faculty composed in fire prevention procedures.